PENGARUH HASIL BELAJAR MAHASISWA DALAM MATAKULIAH PENGANTAR MANAJEMEN DAN MANAJEMEN PEMASARAN TERHADAP HASIL BELAJAR MATAKULIAH KONSULTAN MANAJEMEN PEMASARAN PADA MAHASISWA STIE YPBI JAKARTA PERIODE 2006 – 2010 - Agus Jamaludin (Fakultas Ekonomi Universitas Negeri Jakarta, 2012)
Abstract The purpose of this study to determine the effect of student learning outcomes in the course Introduction to Management and Marketing Management of the learning course Marketing Management Consultant. Basic theory used is the theory of Thorndike. This theory states that the transfer of learning occurs from situation to situation, depending on the number of elements of the course content, manner, method, or purpose which may be incurred in both situations. The research was conducted in Jakarta YPBI STIE student 2006-period ex post facto research is 2010.Metode, sample as many as 20 people taken at random from a population of 35 people. The results obtained from study subjects Introduction to document management, and marketing management and marketing management consultant, lecturer and course records as the author of Introduction to Management and Management Consultant Pemasaran.Variabel consists of three variables: two independent variables, namely course Introduction to Management and Marketing Management, and a variable bound to the Consultant in Marketing Management course. Data analysis techniques required are Multiple regresion are: X1 = a + + b2X2 b3X3, testing hypotheses about the B2 and B3 used a statistical test with 95% confidence level or standard error of 0.05. The result is that the regression equation X1 = X2 +0.2 X3 27.2 +0.4, and 0.39 <B2 <0.41 = 0.95 and 0.18 <B3 <0.22 = 0.45 Keywords: Introduction to Management, Marketing Management, Marketing Management Consultant.